If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(x*(x+1))/2 = 453 // - 453
(x*(x+1))/2-453 = 0
(x*(x+1))/2+(-453*2)/2 = 0
x*(x+1)-453*2 = 0
x^2+x-906 = 0
x^2+x-906 = 0
x^2+x-906 = 0
DELTA = 1^2-(-906*1*4)
DELTA = 3625
DELTA > 0
x = (3625^(1/2)-1)/(1*2) or x = (-3625^(1/2)-1)/(1*2)
x = (5*145^(1/2)-1)/2 or x = (-5*145^(1/2)-1)/2
(x-((-5*145^(1/2)-1)/2))*(x-((5*145^(1/2)-1)/2)) = 0
((x-((-5*145^(1/2)-1)/2))*(x-((5*145^(1/2)-1)/2)))/2 = 0
((x-((-5*145^(1/2)-1)/2))*(x-((5*145^(1/2)-1)/2)))/2 = 0 // * 2
(x-((-5*145^(1/2)-1)/2))*(x-((5*145^(1/2)-1)/2)) = 0
( x-((-5*145^(1/2)-1)/2) )
x-((-5*145^(1/2)-1)/2) = 0 // + (-5*145^(1/2)-1)/2
x = (-5*145^(1/2)-1)/2
( x-((5*145^(1/2)-1)/2) )
x-((5*145^(1/2)-1)/2) = 0 // + (5*145^(1/2)-1)/2
x = (5*145^(1/2)-1)/2
x in { (-5*145^(1/2)-1)/2, (5*145^(1/2)-1)/2 }
| -2y=-8x | | (1/4)-(5/y)=3 | | 7y+4(y-6)=4(y+2)-5 | | p(x)=3x^4-4x^3+x^2+6x-2 | | -2d+8=2(-d+4) | | 3.6x+14.7=.3-1.2x | | .3x+8.6=.65x+10 | | 13-20-(-2)= | | y=-4x^5+2x^4+6x+5 | | 25-2(7+5)= | | 36+35/5*4 | | 4(c-3)-6=6 | | -7(x+2)-18=25+6 | | 141/9-13/18 | | .4+.6x=.53+.5x+1.5 | | 3x^4-4x^3+x^2+6x-2= | | 2x+y=-400 | | -(1-2)-4= | | y=-3x^9+8x^6+7x^5+7 | | w=p(v-l) | | 8-(11-7)= | | 5/9+10 | | (4w-9)(5-w)=0 | | 9-3(-2-5)=30 | | 6m-8=2+9m-11 | | 2(z-1)=4(z+5)-10 | | 5(y-7)/4=-2y | | 2.4x=-8.4 | | 3x-5x=20 | | 1/4x-5=-25 | | x^(2/3)-2x^(1/3)-8=0 | | 11-6y-19=7y+8-5y |